L2 Acquisition Portrayed through the Use of Way Ahead Game by Children in Learning Basic English - Angga Apresa Nuryasin (TEKNOSASTIK, 2018)
This research investigates how students learn Basic English by using Way Ahead game. This study was conducted to identify how effective the use of educational game in acquiring L2 is. Qualitative study was used by the researcher as the research method. The data were collected through conducting several interviews and exploring library study. The case study involved 4 elementary school students as the participants. The background of the research on the role of game in learning L2 is based on Fuscard (2001) and Boyle (2011). The findings of this research are 4 most important roles of game implementation in learning process: (1) pedagogical device, (2) creative ice breakers, (3) engaging students, (4) helping students retain salient points in our teaching. The purpose of the research is to give information over the portrayal of using educational games in learning which is expected to give practical use in teaching Basic English to children as their L2 acquisition.Key Words: L2 acquisition, basic English, Way Ahead game